Risk factors for disease progression in HER2-positive breast cancer patients based on the location of metastases - Huszno, Joanna; Nowara, Elżbieta (Menopause Review/Przegląd Menopauzalny, 2015)
Introduction : Trastuzumab therapy significantly improves progression-free and overall survival in HER2-positive [HER2(+)] breast cancer (BC) patients. However, in most patients with HER2(+) metastatic BC, the disease progress occurred. The aim of this study was to evaluate the clinicopathological risk factors for progression in HER2-positive breast cancer patients during trastuzumab therapy. Material and methods : The analysis included medical records of HER2(+) metastatic BC patients treated with trastuzumab between 2006 and 2013. Results : The most common site of progression during trastuzumab therapy were lungs 25 (39%), central nervous system (CNS) 8 (13%), skin 9 (14%), locoregional lymph nodes 19 (30%), liver 18 (28%) and bone 17 (27%). Patients with lung metastases significantly more often had a history of cancer in the family than women with other metastasis sites (24% vs. 2.6%), p = 0.048. Metastases to lungs occurred also more often during therapy containing trastuzumab with chemotherapy than trastuzumab alone 17/8 (58% vs. 41%), p = 0.043. Central nervous system metastases were observed insignificantly more frequently in postmenopausal women than premenopausal patients 8/0 (22% vs. 0%), p = 0.093. There was reported a tendency to liver metastases in ER-negative tumors 13/20 (72% vs. 44%, p = 0.053). Bone metastases were associated with the positive steroid receptor status (p = 0.019) and second neoplasm in history (p = 0.06). Conclusions : Risk factors for disease progression were the menopausal status (CNS metastases), steroid receptor status (liver, lymph nodes and bone metastases), history of cancer in the family (lung metastases) and history of cigarette smoking (liver metastases).